Unignorable enzyme-specific isotope fractionation for nitrate source identification in aquatic ecosystem - Wang, Shuo; Lyu, Tao; Li, Shengjie; Jiang, Zhuo; Dang, Zhengzhu; Zhu, Xianfang; Hu, Wei; Yue, Fu-jun; Ji, Guodong (Elsevier, 2024)
Nitrate contamination in aquatic systems is a widespread problem across the world. The isotopic composition (δ15N, δ18O) of nitrate and their isotope effect (15ε, 18ε) can facilitate the identification of the source and transformation of nitrate. Although previous researches claimed the isotope fractionations may change the original δ15N/δ18O values and further bias identification of nitrate sources, isotope effect was often ignored due to its complexity. To fill the gap between the understanding and application, it is crucial to develop a deep understanding of isotopic fractionation based on available evidence. In this regard, this study summarized the available methods to determine isotope effects, thereby systematically comparing the magnitude of isotope effects (15ε and 18ε) in nitrification, denitrification and anammox. We found that the enzymatic reaction plays the key role in isotope fractionations, which is significantly affected by the difference in the affinity, substrate channel properties and redox potential of active site. Due to the overlapping of microbial processes and accumulation of uncertainties, the significant isotope effects at small scales inevitably decrease in large-scale ecosystems. However, the proportionality of N and O isotope fractionation (δ18O/δ15N; 18ε/15ε) associated with nitrate reduction generally follows enzyme-specific proportionalities (i.e., Nar, 0.95; Nap, 0.57; eukNR, 0.98) in aquatic ecosystems, providing enzyme-specific constant factors for the identification of nitrate transformation. With these results, this study finally discussed feasible source portioning methods when considering the isotope effect and aimed to improve the accuracy in nitrate source identification.
Keywords: Eutrophication control; Nitrate source identification; Enzyme-specific isotope effects; Stable isotopes